An obvious fact [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2016)
Walt, Henry, and Vic discover much more than they bargained for when they are called in to investigate a hit and run accident involving a young motorcyclist near Devils Tower in this next installment of the Longmire series.